Effects of increasing rejection temperatures on electricity demand for ventilation and cooling in automated metalliferous underground mines - Mochubele, Ekgatlamang Mothusi (My University, 2014)
The South African power crisis and corresponding rising costs experienced since 2008, created a paradigm shift in terms of electricity use. The mining sector is the second highest consumer of electricity with metalliferous mines being accountable for 80% of the total power. Recent studies revealed that underground ventilation and cooling accounts for 30% to 40% of total electricity costs in an underground metalliferous mine. Hence the need to look at ways to reduce electricity consumption in ventilation and cooling. Work has been done on optimising efficiencies of ventilation and refrigeration systems of underground mines. Currently, the high energy consumption is driven by efforts to achieve a thermally acceptable environment for workers (manned) in deep metalliferous mines which is currently between 27ºC (wb) and 29ºC (wb). However, no detailed study has been done looking at increasing thermally acceptable environments for deep level metalliferous mine. In this study the impact of increasing rejection temperature to 40ºC (db) was assessed in the automated (unmanned) scenario at a maximum depth of 2811 metres. Then the power demand was compared with the manned scenario. The results proved that automation in an underground mine has the potential of reducing electricity cost of ventilation and cooling by more than 50%. For example, the production rate of about 200 kilo-tons per month yield an annual cost saving of R71 million on electricity. These cost savings can be used to justify automation systems. Automation removes workers from the hazardous environment and replaces them with equipment which can withstand harsher conditions. The introduction of an automation system in underground mines would not come risk-free. Currently, automation systems have not yet reached a level of removing workers completely from underground.There are instances that would require workers to enter production zones. A Bow-Tie risk analysis was used to show the hazards that workers would be exposed to and prevention controls and responses to mitigate the impact the risks.
A research report submitted to the Faculty of Engineering and the Build Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Engineering Johannesburg, 2014
Keywords: Mine ventilation; Mining engineering; Mine shafts; Heat--Transmission